RELATION BETWEEN ANTHROPOMETRIC PARAMETERS AND THE ADHERENCE TO THE MEDITERRANEAN DIET IN YOUNG ELITE MALE PADDLERS - Vaquero-Cristóbal, Raquel (2018)
The present study aimed to analyze Mediterranean diet adherence and its relationship with anthropometric variables in young elite paddlers. One hundred and ten young male paddlers (mean age: 15.51 ±0.66 years old and mean BMI: 22.35 ± 1.66 kg·m-2) were measured according to International Society for the Advancement of Kinanthropometry guidelines. Mediterranean diet adherence was analyzed using the KIDMED questionnaire. Most of the paddlers presented an excellent adherence to the Mediterranean diet (n=73); meanwhile, 31 showed a medium and six a low adherence. Anthropometric variables, body mass index, somatotype and body composition percentages showed similar values when the paddlers were divided based on their adherence to the Mediterranean diet. Paddlers showed an adequate consumption of cereals, olive oil, dairy products for breakfast, processed baked goods, candy sweets, and fast food. The consumption of fruits, vegetables, fish, legumes, yogurt, cheese, and nuts was lower than recommended. In conclusion, the present study showed that there is not a clear relationship between anthropometric parameters and the Mediterranean diet adherence among young elite male paddlers. Furthermore, most paddlers showed an excellent or medium adherence to the Mediterranean diet.